Comparative study of nondescent vaginal hysterectomy and abdominal hysterectomy at tertiary care centre, Maharashtra - Mujumdar, Sharayu Prashant; Purohit, Priyanka Kunal; Navale, Shwetambari S.; Upadhyay, Chintan M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vaginal route of hysterectomy has distinct health and economic benefits in terms of less morbidity, better postoperative quality of life outcomes, reduced hospital stay and better patient satisfaction. Objectives of current study were to evaluate the appropriate route of hysterectomy (abdominal or vaginal) in terms of intra and post-operative complication, morbidity and blood loss. Methods: This prospective study was done among 100 cases of hysterectomy of which 50 patients underwent NDVH and 50 underwent abdominal hysterectomy. This study included all emergency and booked patients having Size of uterus less than 12 weeks size, adequate uterine mobility, adequate access, adenomyosis, dysfunctional uterine bleeding, chronic PID & fibroid uterus. Results: Study found statistically significantly higher number of the participants with parity 3 & 4 in both the study groups. Bulky uterus followed by 12 and 10 weeks uterus in statistically significantly higher number of the participants of both the study groups. Duration of surgery statistically significantly less in NDVH group compare to TAH group. Fibroid was the main indication of hysterectomy in both the groups. Hemorrhage was the main intra-operative complication in both the groups. Fever & respiratory tract infection was the main post-operative complications in both the groups. Conclusions: Benefits of NDVH over TAH are Cosmetic advantage as less invasive, No discomfort of abdominal incision, shorter operative time, lesser blood loss, lesser intraoperative and postoperative complications, postoperative comfort is more, lesser requirement of postoperative analgesia, early ambulation and shorter hospital stay.